Comparative metabolomics and transcriptomics provide new insights into florpyrauxifen-benzyl resistance in Echinochloa glabrescens - Jin, Wenyong; Xie, Kexin; Tang, Wei; Yang, Yongjie; Zhang, Jianping; Yu, Xiaoyue; Lu, Yongliang (Frontiers in Plant Science, 2024)
Echinochloa glabrescens Munro ex Hook. f. is a weed of the genus Echinocloa (Echinocloa spp.) that occurs frequently in paddy fields, causing serious harm to rice production. Florpyrauxifen-benzyl (FPB) is a foliar-applied herbicide used to control Echinocloa spp. in paddy fields. However, in recent years, with the widespread use of FPB in rice production, FPB-resistant barnyard grasses have been reported. Here, we identified an FPB-resistant E. glabrescens population with a resistance index (RI) of 10.65 and conducted a comparative analysis using untargeted metabolomics and transcriptomics to investigate the differences between an FPB-resistant E. glabrescens population and a susceptible E. glabrescens population after treatment with the recommended field dose of FPB.Our results showed that the FPB-resistant E. glabrescens had 115 differentially accumulated metabolites (DAMs; 65 up-regulated and 50 down-regulated) and 6397 differentially expressed genes (DEGs; 65 up-regulated and 50 down-regulated) compared to the susceptible E. glabrescens. The analysis of DAMs and DEGs revealed that DAMs were significantly enriched in Glutathione metabolism, Arginine and proline metabolism, and Zeatin biosynthesis pathways, while DEGs were mainly enriched in carbon fixation in photosynthetic organisms, photosynthesis, cyanoamino acid metabolism and glutathione metabolism, etc. The glutathione metabolism pathway was found to be significantly enriched for both DEGs and DAMs. Within this pathway, the metabolites (spermine) and genes (GSTU8, GSTU18, GSTF1) may play a pivotal role in the resistance mechanism of FPBresistant E. glabrescens. Furthermore, we demonstrated the presence of GST-mediated metabolic resistance in an FPB-resistant E. glabrescens population by using NBD-Cl. Overall, our study provides new insights into the underlying mechanisms of E. glabrescens resistance to FPB through a comparative analysis of untargeted metabolomics and transcriptomics. Additionally, we identified the GST-mediated metabolic resistance in an FPB-resistant E. glabrescens population, and screened for three candidate genes (GSTU8, GSTU18, GSTF1), which has significant implications for improving the weed management efficacy of FPB in rice production and guiding judicious herbicide usage.